Optimum Koi Herpesvirus DNA Extraction from the Aquaculture Water - Khumaira Puspasari; Ishaaq Saputra; Agustina Kristina Sibuea; Zulhan Efendi Lubis; Firma Firma (Jurnal Perikanan dan Kelautan, 2022)
Koi Herpesvirus (KHV) is one of the viral fish disease in the common carp aquaculture. At present, KHV diagnoses is performed using Polymerase Chain Reaction (PCR) method. However, the effort to extract DNA viruses from environmental samples depends on two fundamental problems: inhibition of the extraction and amplification processes and a very small number of viruses. The small amount of virus load in the water requires a concentration process before further molecular analysis. In this study, the sensitivity of three methods of extraction and purification of viral genetic material from the water, namely deposition with PEG, filtration-elution, and flocculation with antibodies for the detection of KHV from the water with the PCR method was performed. Water samples were collected from Cirata reservoir, West Java which is a site location for carp aquaculture. The organic flocculation cannot be carried out in the present study because anti-KHV antibodies cannot be produced. This is because the amount of virus in the sample used by the vaccine is low. Meanwhile, the precipitation method with PEG cannot produce DNAextract’s although quantity and purity are good enough to be amplified. For the filtration-elution method, both with and without the reconcentration process, a clear band of DNA can be produced after amplification. In conclusion, the filtration-elution method is considered as the most suitable method in obtaining KHV DNA’s taken from the water samples.